Environmental education in ecological restoration - López Castro, Luis Angel (2024)
The educational system must train people responsible for the care and preservation of ecosystems. When there is environmental education in the population, then the awareness towards the implementation of programs and projects is more adequate, the exchange of knowledge dialogues is responsible and community participation becomes a priority. Th e objective of the study was to describe environmental education in ecological restoration. Ethical and axiological questions are assessed in the relationship between environmental education and ecological restoration. Likewise, it is indicated from the conceptualization of environmental economics and ecological economics, a new base infl uence to make environmental education responsible for ecological restoration. Environmental education as a process suggests the obligation to show awareness towards the care of natural resources, while ecological restoration again facilitates ecosystem services. It is concluded that environmental education in ecological restoration promotes interest in the interdependence and interconnection with natural resources efficiently. Together, they contribute to the well-being and sustainable enjoyment of the unitary values of each resource as a heritage of natural identity.